La inserción laboral de personas con discapacidad y su influencia en la imagen corporativa de las tiendas por departamento - Peña Abregu, Karen Solange (2021)
Since 2012, approximately many retailers have implemented job placement programs for people with disabilities. Also, with the Law 29973 that came into force in December 2012, these practices have been strengthened and increased. Whereby, this research seeks to determine to what extent job placement has influence on the corporate image of retails. For the investigation is used a mixed method, applying 300 quizzes, also an interview with an expert about corporate image and another interview with the head of human management of the Saga Falabella retail. The study shows that job placement does positive influence on the corporate image of department stores by approximately 65%.